Сучасний стан системи найпростіших та місце в ній черепашкових амеб Житомирського i Київського Полісся - Алпатова, Оксана; Alpatova, Оksana (Східноєвропейський національний університет імені Лесі Українки, 2014)
Розглянуто основні етапи становлення системи протистів, її сучасний стан та місце в ній черепашкових амеб. Згідно із сучасною системою еукаріот Едля зі співавторами черепашкові амеби належать до двох неспо- ріднених молекулярних кластерів, які не мають таксономічного статусу: Amoebozoa та Rhizaria. Main stages of protist system formation, its modern state and the position of testate amoebae in it are considered. International Commission on nomenclature and taxonomy suggested new of eukaryotes system dy Adl et al. based on the synthesis of morphological and molecular biological data. The authors of this system consider six large groups of eukaryotes (mostly molecular) for which possible morphological characteristics were chosen. Taxon ranks in the suggested system are marked with asterisk, such categories as kingdom and even phylum are absent. According to modern system testate amoebae from Zhytomyr and Kyiv regions of Polissya relate to two uncongeneric molecular clusters with no taxonomic status: Amoebozoa and Rhizaria. So testate lobose amoebae relate to cluster Amoebozoa, subclass Testacealobosia inside an class Tubulinea, and testate filose amoebae – cluster Rhizaria, class Silicofilosea.
Present-day State of Protozoa System and the Position of Testate Amoebae from Zhytomyr and Kyiv Regions of Polissya in It
Keywords: черепашкові амеби; протисти; еукарiоти; систематика; молекулярний кластер; testate amoebae; protists; eukaryotes; taxonomy; molecular cluster